MOTIVASI SISWA MENGIKUTI PEMBELAJARAN DI MADRASAH DINIYAH (Penelitian di Madrasah Diniyah Nurul Falah Dusun Cilumbu Desa Tanjungjaya Kecamatan Rajadesa Kabupaten Ciamis) - Maulidah, Didah; Nurjanah, Hj.; Millah, Saepul (Jurnal Penelitian Pendidikan Islam, 2016)
This study aims to explore and analyze the motivation of students during the learning in madrasah diniyah. The results of the study can be concluded as follows: 1) Learning methods at Madrasah Diniyah Nurul Falah using 6 methods, namely sorogan method, wetonan/ bandongan method, deliberation method, lecture method, rote method and demonstration method/ worship practice; 2) The driving factors of students participating in learning at Madrasah Diniyah Nurul Falah are intrinsic factors consisting of self-interest and strength, then extrinsic factors consisting of parents, community and environment, learning environment; 3) Motivation of students to take part in learning at Madrasah Diniyah Nurul Falah is categorized as sufficient (C).